The case of the disappearing twin: How writing brought me closer to my self - Evans, Kate (European Journal for Qualitative Research in Psychotherapy, 2019)
Using writing as a means of inquiry, I aim to analyse a change over-time in my creative writing and consider what this change tells me about myself. In doing so, I endeavour to explore creative writing as both a research and a therapeutic tool and to be innovative in the presentation of research. I intend to encourage all therapists, academics and researchers to uninhibitedly dive into their creative selves in order to become more reflexive and gain understanding, as well as for the pure enjoyment of it.